Postural adjustment in standing position when catching a ball under unpredictable conditions of the direction to be caught. Issue 2 (February 2023) - Zhang, Wenyu; Sekiguchi, Yusuke; Honda, Keita; Izumi, Shin-Ichi
Abstract: Background: Balanced postural control of the body is associated with two mechanisms: anticipatory postural adjustment and compensatory postural adjustment. Previous studies reported changes in body postural control under unpredictable conditions (interference with closed eyes). Research question: To ascertain whether in contrast with predictable disturbances, there is a difference in muscle activity and center of pressure displacement changes when the direction of the disturbance is unpredictable. Methods: Three examiners stood at 45° to the left, the front, and 45° to the right of the participant to throw the ball to him. 11 healthy young participants were required to maintain their balance in the standing position after receiving the ball in conditions with and without known catching directions. The anticipatory postural adjustment and compensatory postural adjustment integral changes of the muscle activity in the lower limbs and trunk bilaterally and at the center of pressure displacement in the known and unknown conditions were observed. Two-way ANOVA was used to compare the differences in muscle activity and displacement changes. Results: Results showed that the center of pressure in the anticipatory postural adjustment and compensatory postural adjustment in the posterior direction with known catching direction was significantly shorter than those without. Integration of electromyogram in anticipatory postural adjustment of the right soleus (p = 0.023) was associated with higher muscle activities in the unknown than known conditions. Integration of electromyogram in compensatory postural adjustment of the right tibial anterior (p = 0.004), right rectus femoris (p = 0.023) and left rectus abdominis (p = 0.038) in unknown catching direction had significantly greater muscle activity than those without. When the direction of the perturbation is unpredictable, the central nervous system may initiate and induce greater center of pressure changes in the posterior direction with changes in several muscular activities to ensure postural control.